Diagnostic reproducibility of the 2018 Classification of Gingival Recession Defects and Gingival Phenotype: A multicenter inter- and intra-examiner agreement study - Pini Prato, Giovanpaolo; Di Gianfilippo, Riccardo; Pannuti, Claudio M.; Allen, Edward P.; Aroca, Sofia; Avila-Ortiz, Gustavo; Bouchard, Philippe; Cairo, Francesco; Chackartchi, Tali; Cortellini, Pierpaolo; Franceschi, Debora; Mahajan, Ajay; et al. (My University, 2023)
Background: The aim of this study was to investigate the inter- and intra-examiner agreement among international experts on the diagnosis of gingival recession defects using the 2018 Classification of Gingival Recession Defects and Gingival Phenotype as proposed in the 2017 World Workshop. Methods: Standardized intraoral photographs from 28 gingival recession defects were evaluated twice by 16 expert periodontists. Recession type (RT), recession depth (RD), keratinized tissue width (KTW), gingival thickness (GT), detectability of the cemento-enamel junction (CEJ), and presence of root steps (RS) were recorded and used for the analysis. Intra- and inter-examiner agreements were calculated for individual variables and for the overall classification. Intraclass correlation coefficient with 95% CI was used for RD and KTW; Kappa with 95% CI was used for GT, CEJ, and RS; quadratic weighted Kappa with 95% CI was used for RT. Results: Overall intra- and inter-examiner agreements were highest for KTW (0.95 and 0.90), lowest for GT (0.75 and 0.41), with the other variables in between (RD: 0.93 and 0.68, RS: 0.87 and 0.65, RT: 0.79 and 0.64, CEJ: 0.75 and 0.57). Overall intra- and inter-examiner agreements for the matrix were 62% and 28%, respectively. Significant effects existed between one variable's measurement and other variables’ agreements. Conclusions: The 2018 Classification of Gingival Recession Defects and Gingival Phenotype is clinically reproducible within the examiners, and when the variables forming the matrix are analyzed individually. The between-examiner agreement for the complete matrix showed lower reproducibility. The agreement was highest for KTW and RD, and least for GT.
Keywords: classification; connective tissue; gingiva; gingival recession; periodontics; phenotype; tooth root